OP0127 Association of TYK2 with Systemic Sclerosis, A New Locus in the IL-12 Pathway. (9th June 2015) - Bossini-Castillo, L.; Lopez-Isac, E.; Guerra, S.; Assassi, S.; Simeon, C.P.; Carreira, P.E.; Ortego-Centeno, N.; Beretta, L.; Lunardi, C.; Riemekasten, G.; Witte, T.; Hunzelmann, N.; et al.
Abstract : Background: Systemic sclerosis (SSc) is a chronic connective tissue disorder with the highest mortality of any autoimmune disease. SSc is a complex disease with a clear genetic component. This genetic susceptibility has been supported by a number of well-powered genetic association studies. In this regard, it is remarkable that several SSc genetic markers have been reported in the IL-12 pathway ( IL12A, STAT4, IL12RB2, IL12RB1 ). Furthermore, multiple clinical and experimental evidences have shown that this pathway is altered in SSc patients. TYK2 encodes the Tyrosine kinase 2 enzyme, which mediates the signaling of IL-12 receptor. Objectives: We aimed to analyze the association of the TYK2 locus with SSc susceptibility. Methods: The complete set of individuals included in this study reached 4, 985 SSc patients and 11, 621 healthy controls of European ancestry from Spain, Germany, The Netherlands, USA, Italy and United Kingdom. Initially, we analyzed all the polymorphisms located in the region that encompasses the TYK2 coding sequence and 20 kb up and downstream, in a previously published Immunochip-based dense genotyping study. We identified a common single nucleotide polymorphism (SNP), the V362F variant (rs2304256) and three rare variants: P1104A (rs34536443), A928V (rs35018800) and I684S (rs12720356), as the genetic markers that better explained the observed association in the region. Then, these variants were followed up in additional cohorts. Association and dependence relations were tested using logistic regression and conditional logistic regression, and pooled analyses were performed using the inverse variance method. Results: Our pooled analysis showed that V362F variant reached the genome-wide significance level ( P =2.00x10 -10, OR =0.84), while P1104A (rs34536443), A928V (rs35018800) and I684S (rs12720356) remained significant ( P =8.61x10 -3, OR=0.79; P =1.95x10 -4, OR=0.49; P random =0.016, OR=0.84, respectively). The analyses carried out for the main clinical features revealed that the observed association signals relied on the whole disease. Furthermore, our results revealed that the association of TYK2 with SSc was dependent on the interaction between the P1104A, A928V and I684S rare variants and that the previously observed association for the autoimmune related V362F variant, corresponded to a synthetic association dependent on the association of the three previously mentioned rare variants. Conclusions: We report for the first time the association of TYK2 variants with SSc. Moreover, our data support that the highly significant association of a previously known autoimmune disease marker, the V362F variant (rs2304256), is dependent on the effect of three non-synonymous rare variants in this locus . Disclosure of Interest: None declared